Expression and specific activities of carbamoyl phosphate synthetase 1 in chronic hypoxic rats (Medical Journal of Indonesia, 2016)
Background: Urea biosynthesis is a very important process in the liver which needs ATP, CO2 and functional mitochondria or aerobic condition. Liver can adapt to hypoxic condition, generally and locally. This study aimed to analyze the effect of chronic hypoxia on liver urea biosynthesis as indicated by the level and specific activity of mRNA of carbamoyl phosphate synthetase 1 (CPS1), a key enzyme in urea biosynthesis in hypoxic rats. Methods: 20 male Sprague-Dawley rats were placed in hypoxic chamber supplied by a mixture of 10% O2 and 90% N2. Five rats were sacrificed at 1, 3, 5, and 7 days after exposure. Liver homogenates were analyzed for HIF-1 (hypoxia inducible factor-1) by ELISA, CPS1 mRNA by real time RT-PCR and CPS1 enzymatic specific activities by Pierson method. Data were analyzed by ANOVA test and Pearson correlation. Results: The HIF-1 in liver increased significantly, as well as CPS1 mRNA and CPS1 enzymatic activities (p<0.05). There was a strong correlation (r=0.618; p<0.01) between the level of CPS1 mRNA and CPS1 enzymatic activities, moderate correlation between HIF-1 and CPS1 mRNA (r=0.419; p<0.05) but no correlation between HIF-1 and CPS1 enzymatic activities. The study indicated that urea biosynthesis in liver was affected by hypoxia and partially under HIF-1 regulation. The study also found increase of urea and NH3 biosynthesis related to proteolysis as indicated by the decrease of total body weight and liver weight. Conclusion: There was an increase in the expression and specific activities of CPS1 in urea biosynthesis as a result of increasing proteolysis in chronic hypoxic condition.